Wykorzystanie wybranych metod analizy wielowymiarowej do klasyfikacji funduszy inwestycyjnych - Salamaga, Marcin (An Application of Selected Multivariate Analysis Methods for the Classification of Mutual Funds, 2008)
In the paper there are presented factor analysis for variables which describe mutual funds. Next the author proposes the application of Ward's clustering method and A-means method for the classifications of mutual funds on the basis of experience in management assets, results of investment activity and investment risks and efficiency measures of portfolio management. The author uses the market, economic and financial ratios of the mutual funds in Poland from 1999 to 2005.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 409-415